2019
DOI: 10.14202/vetworld.2019.729-734
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with Cryptosporidium spp. infection in local breed of dogs in Enugu State, Nigeria

Abstract: Aims: Cryptosporidiosis is an important zoonotic disease of major public and veterinary concern. The disease affects humans and a variety of animal species including the domestic dog. This study aimed to determine the prevalence and risk factors associated with Cryptosporidium spp. infection in local breed of dogs from different homes and those presented at veterinary hospitals and clinics in Enugu State, Nigeria. Materials and Methods: A total of 203 fresh fecal samples were collected from domestic dogs in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
1
2
0
1
Order By: Relevance
“…In our study, no significant relation was found between the fecal consistency and the presence of Cryptosporidium. This is consistent with the observations of others (Gentil et al 2017;Itoh et al 2019;Eze et al 2019;Li et al 2019). On the other hand, Taghipour et al (2020) observed a positive association between a Cryptosporidium infection and diarrhea in dogs performing a meta-analysis of published studies.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, no significant relation was found between the fecal consistency and the presence of Cryptosporidium. This is consistent with the observations of others (Gentil et al 2017;Itoh et al 2019;Eze et al 2019;Li et al 2019). On the other hand, Taghipour et al (2020) observed a positive association between a Cryptosporidium infection and diarrhea in dogs performing a meta-analysis of published studies.…”
Section: Discussionsupporting
confidence: 94%
“…detected in the feces of sampled dogs recapitulates previous reports in Nigeria (Ayinmode et al, 2016;Ezema et al, 2019;Kamani et al, 2021) and outside Nigeria (Abere et al, 2013;Ngui et al, 2014;Torres-Chablé et al, 2015). The prevalence rates of 33.24%, 36.45%, and 41.67% for Ancylostoma spp., Cryptosporidium spp., and Toxocara spp., respectively, have been reported among dogs in Nigeria (Ugbomoiko et al, 2008;Idika et al, 2017;Eze et al, 2019). In countries outside Nigeria, the prevalence rates of 33.04%, 33.46%, and 64.71% for Ancylostoma spp., Toxocara spp., and Cryptosporidium spp., respectively, have been reported among dogs (Bahrami et al, 2011;Ayan and Kilinç, 2020;Ilic et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies were epidemiological surveys of Cryptosporidiosis around the world. In early studies, microscope-based morphological methods and antigen detection assays were commonly used to detect Cryptosporidium oocytes (35)(36)(37)(38)(39)(40)(41)(42). The use of molecular tools has led to the identification of several zoonotic Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%